Adaptively robust rotary speed control of an anchor-hole driller under varied surrounding rock environments. (May 2019) - Guo, Yinan; Cheng, Wei; Gong, Dunwei; Zhang, Yang; Zhang, Zhen; Xue, Guanghui
Abstract: A fixed rotary speed is adopted when drilling different rocks manually, resulting in an inefficient operation. Taking the characteristics of the electro-hydraulic servo component and the proportional valve in the anchor-hole driller into consideration, an adaptively robust control is designed to track the optimal rotary speed of the anchor-hole driller under the changing surrounding rocks, with the purpose of achieving an efficient operation. To fulfill this task, the optimal rotary speed of the anchor-hole driller under the changing surrounding rocks is firstly estimated in terms of the measured pressure and torque. Following that, an adaptively robust controller is designed for the rotation speed of the anchor-hole driller with nonlinear, unknown, and time-varying parameters. Finally, a compensation strategy is developed to alleviate the negative influence of dead-zone in the three-position four-way proportional valve. The proposed control strategy is applied to two scenarios of the roof rock stratums, and compared with the existing approach. The experimental results show that the proposed controller has a capability of rapidly tracking the optimal rotary speed with a small overshoot and oscillation, which is beneficial to improving the drilling efficiency. Highlights: Estimating the optimal-reference rotary speed under the changing surrounding rocks. Designing an adaptively robust controller for the rotation speed of the driller. Developing a compensation strategy to alleviate the negative influence of dead-zone.